RESIDUAL STOCHASTIC PRECEDENCE ORDER. Issue 3 (July 2021) - Misra, Amit Kumar; Gupta, Vaishali; Misra, Neeraj
Abstract : The aim of this paper is to introduce a new stochastic order based on the residual lifetimes of two nonnegative dependent random variables and the stochastic precedence order. We develop some characterizations and preservation properties of this stochastic order. In addition, we study some of its reliability properties and its relation with other existing stochastic orders. One of the possible applications in reliability theory has also been discussed.